Mechanism of immune escape mediated by T cell depletion induced by TOX signaling pathway in cervical cancer microenvironment - LIU Dan, ZHANG Guxiang, XIE Dan, XU Yan, XIE Chengfang, TANG Yuxi (Zhongguo aizheng zazhi)
Background and purpose: Immune checkpoint blockade (ICB) has become a promising strategy for treating cervical cancer (CC), but terminal T cell depletion still limits the therapeutic efficacy of ICB. The deletion of sorting nexin-9 (SNX9) can inhibit thymocyte selection-associated high mobility group box protein (TOX), alleviate T cell exhaustion, and provide new ideas for preventing T cell exhaustion and enhancing the efficacy of cancer immunotherapy. Therefore, this study aimed to explore the immune escape mechanism mediated by the depletion of CD8+ T cells induced by the SNX9/TOX signaling pathway in the CC microenvironment. Methods: Fifty-four peripheral blood samples were collected, including 18 from CC patients, 18 from patients with high-grade squamous intraepithelial lesions (HSIL) and 18 from subjects with normal cervix. In addition, the study collected 153 pairs of CC and adjacent tissues from patients who received operation in our hospital for the first time. Clinicopathological features, tumor stages, follow-up records and other relevant clinicopathological data of CC patients were obtained from hospital records. The research was approved by the ethics committee of Changsha Fourth Hospital (approval number: 20220206). A total of 24 mice were randomly assigned to the following four groups: immunoglobulin G (IgG) group, Anti-SNX9 group, Anti-programmed death-1 (PD-1) group and Anti-SNX9+Anti-PD-1 group, with 6 mice in each group. Each group received intraperitoneal injection of blocking antibody and isotype control treatment respectively. ELISpot was used to detect the ability of CD8+ T cells to secrete tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ). The expressions of TOX and SNX9 in cervical cancer tissues were detected by western blot and immunohistochemistry. Results: The expressions of SNX9 and TOX mRNA in peripheral blood mononuclear cell (PBMC) of CC patients were higher compared with HSIL and normal controls (P<0.05). The positive cell level of SNX9 and TOX immunohistochemical score were higher in CC tissue than in adjacent tissues (t=18.63, 21.10, P<0.001). The high expression of SNX9 in CC was related to low differentiation/undifferentiation, tumor size, parauterine infiltration, vaginal infiltration, late FIGO stage and pelvic lymph node metastasis (P<0.05). Compared with the low expression group of SNX9, the overall survival time of CC patients in the high expression group of SNX9 was shorter (P<0.05). The percentage of CD8+SNX9+ T cells was significantly higher in CC patients than in normal controls and HSIL patients (P<0.05). The ability of CD8+SNX9+ T cells to secrete cytokines (TNF-α and IFN-γ) was significantly lower compared with CD8+SNX9- T cells (P<0.05). Compared with the Anti-SNX9 group, the growth and proliferation of cervical tumor, the expression of SNX9 and TOX protein in tumor tissue in the Anti-SNX9+Anti-PD-1 group further decreased (P<0.05), and the level of infiltrating CD8+ T lymphocytes in tumor tissue and the ability of CD8+ T lymphocytes to secrete functional factors TNF-α and IFN-γ further increased (P<0.05). Conclusion: SNX9/TOX signaling pathway exhibits enhanced activity in patients with cervical cancer and mouse models, and is related to immunosuppression. Targeting SNX9/TOX signaling pathway may be a potential therapeutic strategy for CC.